From Building Blocks to Architects Empowering Learners for Success - Reyes Juana Mahissa (Universidad Nacional de Colombia, 2002)
Although our ultimate goal is to enable our learners to become autonomous and efficient in their use of the foreign language, whether or not they have the opportunity to ever live and interact in a foreign language setting, our work as teachers must involve a conscious analysis of the different factors involved in this process, as well as the conscious effort to put all the intervening factors into action. Furthermore, it is our responsibility to develop the learners¿ thinking skills as they increase their competence in the target language and at the same time make them aware of their responsibility for their own processes and success by enhancing their autonomy and making them aware of the value of learning strategies. It is our task as teachers to be present on this journey and guide our learners towards becoming architects and masters of their own foreign language construct. In order for this journey to be a successful one, we must make sure we provide the learner with a correct supply of building blocks. In this paper we present an analysis of the main components comprised in teaching English as a foreign language, including a historical overview of methods, approaches, strategies, the concept of learner¿s autonomy, social and psychological factors, aiming at contributing to every teacher¿s reflection on his/her task in the school context.